Conclusioni - Wataghin, Gisella Cantino (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2005)
Abstract Starting from the contributions presented in the three main sections of the Colloque, some general remarks are presented, with the aim of underlining the main results of the meeting and at the same time of suggesting possibilities of further investigations. They concern the nature and limits of the material sources; the connection between their different classes and their historical interpretation; the relations between the dress worn and the dress represented; the contribution of the study of cloth and clothing to a better understanding of Late Antiquity.